Epigenome Engineering in Cancer: Fairytale or a Realistic Path to the Clinic? - Falahi, Fahimeh; Sgro, Agustin; Blancafort, Pilar (Frontiers in Oncology, 2015)
Epigenetic modifications such as histone post-transcriptional modifications and DNA methylation organize the DNA in the nucleus of eukaryotic cells and are critical for the spatio-temporal regulation of gene expression. These epigenetic modifications are reversible and precisely regulated by epigenetic enzymes. In addition to genetic mutations, epigenetic modifications are highly disrupted in cancer relative to normal tissues. Many epigenetic alterations (epi-mutations) are associated with aberrations in the expression and/or activity of epigenetic enzymes. Thus, epigenetic regulators have emerged as prime targets for cancer therapy. Currently, several inhibitors of epigenetic enzymes (epi-drugs) have been approved for use in the clinic to treat cancer patients with hematological malignancies. However, one potential disadvantage of epi-drugs is their lack of locus-selective specificity, which may result in the over-expression of undesirable parts of the genome. The emerging and rapidly growing field of epigenome engineering has opened new grounds for improving epigenetic therapy in view of reducing the genome-wide “off-target” effects of the treatment. In the current review, we will first describe the language of epigenetic modifications and their involvement in cancer. Next, we will overview the current strategies for engineering of artificial DNA binding domains in order to manipulate and ultimately normalize the aberrant landscape of the cancer epigenome (epigenome engineering). Lastly, the potential clinical applications of these emerging genome-engineering approaches will be discussed.